Curso-Taller - Valentinuzzi, M. E.; Melul, Sara; Lindig, Miguel; Maass, Roberto (Revista Mexicana de Ingenieria Biomedica, 2018)
Técnicas de medición no-invasivas de parámetros fisiológicos: sistema cardiopulmonar